O desenvolvimento da alfabetização científica de alunos do primeiro ciclo do ensino fundamental utilizando mapas conceituais - Tavares, Simone (2023)
This research started with the planning and execution of Didactic Sequences in the area of ​​Science, using the construction of a Conceptual Map as a didactic resource for the development of scientific literacy. The activities were carried out by students in the 4th year of Elementary School I, in a post-pandemic reality where relationships were still apathetic, based on their experimental experiences, the resocialization process, developed in a municipal public school in the city of Sorocaba. The Didactic Sequences (SDs) elaborated started from the pedagogical proposals referring to the 4th year, thus, the Water theme was the content adopted following the following strategies: classes and activities on the school Blog, presentation of seminars, carrying out experiments and construction of Conceptual Maps . The research was supported by the theoretical assumptions of Sasseron and Carvalho, Ausubel and Novak, which point to the need to re-dimension the scientific work at school, based on the knowledge of the world that students already have, based on Meaningful Learning through the construction Conceptual Maps and the development of Scientific Literacy. The methodology used is part of a qualitative, descriptive and interpretative approach. For data collection, recordings of the classes were used, the debate of the members of each group and the Conceptual Maps constructed by the students, with the aim of analyzing the resocialization and the development of Scientific Literacy. The results showed that the Conceptual Maps provide an active involvement of the students in the process, showing us in their dialogues, the interaction between peers, the resocialization of each one in the school environment, thus providing learning, living together in a meaningful way, offering possibilities of advancing the exchange of knowledge and collaborating for the development of scientific literacy.